2023
DOI: 10.3390/jintelligence11090184
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Differences in Amnestic Mild Cognitive Impairment and Healthy Cognition: A Cross-Sectional Study Employing Online Measures

Grigoria Bampa,
Magdalini Tsolaki,
Despina Moraitou
et al.

Abstract: This study aimed to examine metacognitive abilities in individuals diagnosed with amnestic mild cognitive impairment (aMCI) by using online metacognitive measures during cognitive tasks. A total of 100 participants were enrolled, all aged 50 or older (mean age = 61.98; SD = 6.27), and with a minimum of six years of education (mean = 14.95; SD = 2.94). The sample included 50 individuals with aMCI (34 females) and 50 healthy controls (HC) (33 females). Both groups underwent metacognitive versions of memory tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Yet, compared to cognitively healthy older adults, they display less accuracy when monitoring their performance during task engagement [23][24][25][26]. Accordingly, in a previous work by our team, we found that people with MCI although they were aware of their struggles during task engagement, as reflected by their confidence ratings, they were less accurate in their decisions to choose between wrong and right responses compared to cognitively healthy individuals [27]. Further, previous evidence about the difficulties that people with MCI have with prospective and not retrospective memory self-monitoring abilities [23] shows the need for training specific aspects of metamemory in MCI.…”
Section: Introductionmentioning
confidence: 45%
“…Yet, compared to cognitively healthy older adults, they display less accuracy when monitoring their performance during task engagement [23][24][25][26]. Accordingly, in a previous work by our team, we found that people with MCI although they were aware of their struggles during task engagement, as reflected by their confidence ratings, they were less accurate in their decisions to choose between wrong and right responses compared to cognitively healthy individuals [27]. Further, previous evidence about the difficulties that people with MCI have with prospective and not retrospective memory self-monitoring abilities [23] shows the need for training specific aspects of metamemory in MCI.…”
Section: Introductionmentioning
confidence: 45%
“…It is important to note that this study is part of a broader project wherein participants underwent supplementary neuropsychological tests. The differences in cognitive performance between the two groups based on these scores are detailed in another publication by our team ( Bampa et al, 2023 ). The neuropsychological assessment included a variety of tools: The Geriatric Depression Scale ( Yesavage et al, 1982 ; Fountoulakis et al, 1999 ), the Beck Depression Inventory ( Beck et al, 1961 ), the Beck Anxiety Inventory ( Beck et al, 1988 ), and the Short Anxiety Screening ( Sinoff et al, 1999 ; Grammatikopoulos et al, 2010 ) were implemented to rule out affective disorders.…”
Section: Methodsmentioning
confidence: 99%
“…The extensive neuropsychological damage and progressive cerebral atrophy that characterize MCI may lead to inaccurate recognition of deficits, with the loss of awareness marking a transitional point from MCI to dementia [ 30 ]. The inability to metacognitively assess abilities decreases even from the initial stages, reaching a percentage up to 60%, with the individuals underreporting or even distorting their symptoms, highlighting a gap between metacognitive self-awareness and accurate self-evaluation [ 18 , 31 ]. A similar study found that 23% of drivers with MCI had reduced metacognitive awareness of their deficiencies [ 32 ].…”
Section: Introductionmentioning
confidence: 99%